Alteration of thiol-disulphide homeostasis in acute tonsillopharyngitis. (3rd September 2017) - Kara, Soner Sertan; Erel, Ozcan; Demirdag, Tugba Bedir; Cura Yayla, Burcu Ceylan; Gulhan, Belgin; Neselioglu, Salim; Polat, Meltem; Kalkan, Gokhan; Tapisiz, Anil; Tezer, Hasan
Abstract : Objective : Thiol-disulphide homeostasis (TDH) has a critical role in various clinical disorders. We aimed to assess the association of TDH with acute tonsillopharyngitis (AT) in children. Methods : This study included 94 (73 viral and 21 bacterial) tonsillopharyngitis patients and 88 control children. Their native thiol, total thiol, and disulphide levels were measured. Results : Viral and bacterial tonsillopharyngitis patients had lower native thiol levels compared with healthy children ( P  < 0.001 and P  = 0.008, respectively). Both groups had lower total thiol levels compared with control children ( P  = 0.002 for viral, P  = 0.011 for bacterial). The disulphide levels were lower in bacterial than in viral tonsillopharyngitis patients ( P  = 0.04), and there was a significant difference between viral tonsillopharyngitis patients and the control group ( P  < 0.001). The native/total thiol ratio in each patient group was lower than in the control group ( P  < 0.001 for viral, P  = 0.017 for bacterial). The disulphide/native thiol and disulphide/total thiol ratios were significantly higher in viral ( P  < 0.001 for both) and bacterial tonsillopharyngitis patients ( P  = 0.017 for both) than in healthy children. In all patients, a correlation was found between the levels of C-reactive protein (CRP) and native thiol ( r  = −0.211, P  = 0.04), CRP and total thiol ( r  = −0.217, P  = 0.036), white blood cell (WBC) and native thiol ( r  = −0.228, P  = 0.002), WBC and total thiol ( r  = −0.191, P  = 0.01), and WBC and disulphide ( r  = 0.160, P  = 0.03). Discussion : TDH is altered in AT in children. The alteration is more prominent in viral than in bacterial tonsillopharyngitis.